2018
DOI: 10.1101/459156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-1 subtype C with PYxE insertion has enhanced binding of Gag-p6 to host cell protein ALIX and increased replication fitness

Abstract: Human immunodeficiency virus type 1 subtype C (HIV-1C) has a natural deletion of a YPxL motif in its Gag-p6 late domain. This domain mediates the binding of Gag to host cell protein ALIX and subsequently facilitates viral budding. In a subset of HIV-1C infected individuals, the tetrapeptide insertion PYxE has been identified at the deleted YPxL motif site. Here, we report the consequences of PYxE insertion on the interaction with ALIX and the relevance regarding replication fitness and drug sensitivity. In our… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It has been suggested that Gag can be in a compact conformational structure when in solution or an extended conformational structure when bound to the plasma membrane when still at the immature non-processed state, although these observations were demonstrated with Gag molecules that are lacking the P6 domain (29). Gag is predominantly localized at the plasma membrane (16,30,31), and the P6 domain plays an important role prior and during the virion assembly phase (15). Therefore, this domain is exposed to binding to other viral and host cell proteins and thus also exposed for targeting by GrM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that Gag can be in a compact conformational structure when in solution or an extended conformational structure when bound to the plasma membrane when still at the immature non-processed state, although these observations were demonstrated with Gag molecules that are lacking the P6 domain (29). Gag is predominantly localized at the plasma membrane (16,30,31), and the P6 domain plays an important role prior and during the virion assembly phase (15). Therefore, this domain is exposed to binding to other viral and host cell proteins and thus also exposed for targeting by GrM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this domain is exposed to binding to other viral and host cell proteins and thus also exposed for targeting by GrM. Even though only a relatively small 2 kDa C-terminal part of the P6 late domain is being cleaved off, this exposed domain is important for its interaction with host cell protein ALIX and serves as a binding domain for HIV-1 accessory protein Vpr (16,(32)(33)(34)(35)(36)(37). The GrM cleavage site is directly after the ALIX binding motif and cleavage could disturb the interaction of ALIX with Gag and thereby affecting the budding of virions from the plasma membrane (16,33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations